Somatic Criticism Project - Dziadek, Adam (Cross-Roads, 2018)
This book illustrates the problems connected with the body and the sign: the real body and the body of the text, somaticism and semiology (both as a general sign theory and in the medical sense as «symptomatology»). The author seeks to derive a more general principle from these two words, referring to the representation of experience in different literary texts. If we are talking about the representation of experience, we cannot, by any means, ignore the body that becomes the essential point of reference for human experience. This general principle aims at creating a matter of concept, a somatic criticism project, which is closely related to the issue of rhythm in literary texts - a rhythm understood as an intermediary between the body and the sense of the text.